In search of sustainable urban green infrastructure through an ecological approach - Olsson, Ida (2018)
One of the greatest challenges of today’s urban development is the formation of sustainable environments. Over the past several decades, there has been a shift in the global population from a more rural allocation to an urban one, resulting in the densification of cities and subsequent fragmentation of green areas. As green areas are being claimed for different types of development, they are becoming increasingly dispersed and receive a reduced ability to serve functions of value for both humans and the environment. Amplifying the amount of impervious surfaces, stormwater runoff and barrier effects in the urban environment as a consequence. Moreover, urban environments have become a platform for the creation of globally homogenous landscapes, displaying similar methods of design and construction. This use of similar plant material and planning principles for urban spaces is leading to a loss of biodiversity and increasing costs with regard to management and maintenance. Thus, over the past several decades new design aesthetics for urban areas have begun to emerge which are more strongly founded in ecological approaches to design. These practices can be addressed on different scales and are more focused on the context of site, seeking to regenerate and strengthen its natural processes. This master thesis seeks to investigate such ecological approaches to design by studying the green infrastructure of an urban environment anticipating new development and growth. One region, currently facing such changes is the municipality of Danderyd, Sweden. In consequence, there is a need to evaluate existing green areas and plan for future development of the green infrastructure. This master thesis aims to study the green infrastructure of the municipality in order find ecological approaches to support a more sustainable development. A literature study was performed concerning the concepts of green infrastructure and ecological design. Further, a case study was conducted investigating the municipality on three different scales; large, intermediate and small. Finally, guiding principles regarding future development of the green infrastructure were presented for each scale. Approaches concerning the protection of existing natural areas, increasing biodiversity, stormwater management, green connections and creating stewardship opportunities were shown to be of particular significance. Further research questions concerns the development of more detailed, site specific solutions and requires additional knowledge stretching between professional competencies. Thus, this master thesis can be seen as an initial step in order to support a sustainable green infrastructure in the municipality of Danderyd and environments with similar conditions. Additionally, it constitutes a means of sharing experiences gained with regard to ecological design solutions in this particular region.